Collaboration for Empowerment of Educational Services at Sultan Zainal Abidin University, Malaysia - Hamdi, Tegar Alhilal; Nugroho, Aziz; Anugrah, Farhan; Prasetyo, Andri Eko; Amiroh, Amiroh; Ibrahim, Abdullah (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Barriers to international collaboration include cultural differences, language, and education systems, as well as administrative, and logistical challenges, and resistance to innovation. The purpose of this community service is to enhance the quality of education through curriculum development, international collaboration, teaching innovations, and global educational awareness. Implementation method: using a PAR approach, involving all parties, with supporting media such as laptops, office supplies, activity implementation, and evaluation. The results of the activities show very positive outcomes with a significant impact on participants. Evaluations of ICFASS24, FlexS, and Mandarin Language Classes indicate high satisfaction levels, with the majority of participants rating on a scale of 5. ICFASS24 successfully expanded academic insights and developed participants' managerial skills, while FlexS was effective in building excellent personality and self-development through an Islamic psychospiritual approach. The Mandarin Language Class provided significant benefits in improving language skills and participants' global perspectives, enhancing teaching competencies, and preparing them to face global challenges. Conclusion: This service successfully enhanced the quality of education, expanded academic insights, developed skills, and prepared participants to face global challenges.